Fiscal Rules to Tame the Political Budget Cycle : Evidence from Italian Municipalities - Forni, Lorenzo; Bonfatti, Andrea (Washington, D.C. : International Monetary Fund, 2017)
The paper provides evidence that fiscal rules can limit the political budget cycle. It focuses on the application of the Italian fiscal rule at the sub-national level over the period 2004-2006 and shows that: 1) municipalities are subject to political budget cycles in capital spending; 2) the Italian subnational fiscal rule introduced in 1999 has been enforced by the central government; 3) municipalities subject to the fiscal rule show more limited political budget cycles than municipalities not subject to the rule. In order to identify the effect, we rely on the fact that the domestic fiscal rule does not apply to municipalities below 5,000 inhabitants. We find that the political budget cycle increases real capital spending by about 35 percent on average in the years prior to municipal elections and that the sub-national fiscal rule reduces these figures by about two thirds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet